2019
DOI: 10.14419/ijet.v7i4.14.27582
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Par-Frying and Calcium Propionate on the Quality of Frozen Curry Puff

Abstract: This study proves that the application of par-frying method and addition of calcium propionate able to prolong the shelf life and preserve the quality of frozen pastry curry puff during distribution and storage after exposure to fluctuating temperature. Par-fried curry puff added with 0.1% calcium propionate produce lower moisture content, oil uptake and weight loss than non-par fried puff. In addition, par fried curry puff was capable of preventing any visible black spots (after 4 weeks storage) which are rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Oxidation reaction will cause bran particles naturally present in flour, one of the FCCCP ingredients for curry puff skin, to become dark brown or black spots (Cauvin, 2001). Similarly, Hussain et al (2018) found that curry puff samples (control) exposed to temperature fluctuation during storage formed black spots on the surface of the skin after four weeks. However, Sultana et al (2014) found that black spots detected on chapatti samples stored at a refrigerated temperature of 6 °C on day 30 were associated with a low water activity of samples that led to fungal growth.…”
Section: Microbiological Quality During Storagementioning
confidence: 78%
See 1 more Smart Citation
“…Oxidation reaction will cause bran particles naturally present in flour, one of the FCCCP ingredients for curry puff skin, to become dark brown or black spots (Cauvin, 2001). Similarly, Hussain et al (2018) found that curry puff samples (control) exposed to temperature fluctuation during storage formed black spots on the surface of the skin after four weeks. However, Sultana et al (2014) found that black spots detected on chapatti samples stored at a refrigerated temperature of 6 °C on day 30 were associated with a low water activity of samples that led to fungal growth.…”
Section: Microbiological Quality During Storagementioning
confidence: 78%
“…Oxidation reaction will cause bran particles naturally present in flour, one of the FCCCP ingredients for curry puff skin, to become dark brown or black spots(Cauvin, 2001). Similarly,Hussain et al (2018) found that curry puff samples (control) exposed to temperature fluctuation…”
mentioning
confidence: 87%